DISCOURSE ANALYSIS OF SOCIAL COGNITION ON ELEMENTS OF KNOWLEDGE IN THE NOVEL OF ORDINARY PEOPLE TEUN A. VAN DIJK'S THEORY - Filia Dwi Lestari; Hasan Suaedi; Astri Widyaruli Anggraeni (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This research article discusses social cognition discourse in the element of knowledge in Andrea Hirata's novel The Ordinary People. Critical discourse analysis is an effort made to explain a text that occurs in a social phenomenon that is useful to know the interests within it. Social cognition is an important element in the process of forming views in a discourse that occurs within society. Especially in the element of knowledge that discusses factual beliefs shared by groups or cultures, with this the author will express his discourse based on knowledge gained from personal or group experience. This study aims to describe social cognition, especially the element of knowledge in the main character in the novel "Orang-Orang Biasa." The method in this study uses a type of qualitative research by analyzing a text in the novel. The data collection techniques in this study are reading, marking, and recording. The researcher reads the novel "Orang-Orang Biasa" thoroughly to find data, then the researcher marks the sentences and quotes that contain knowledge of social cognition. Furthermore, by recording the data obtained from the novel. In this study, the researcher uses an analysis technique, namely using the distribution method with advanced techniques. The advanced technique in the distribution method used in this study is in the form of changing the form. The results of the analysis indicate that there are elements of social cognition knowledge conveyed by the author through sentences and quotes from the main character in the text of the novel "Orang-Orang Biasa" which consists of three knowledge. The knowledge is (a) the explicit expression of knowledge, (b) implicit knowledge, (c) contextual knowledge.